Harnessing the Prevention Benefits of Antiretroviral Therapy to Address HIV and Tuberculosis - Granich, Reuben (Bentham Science Publishers, 2011)
After 30 years we are still struggling to address a devastating HIV pandemic in which over 25 million people have died. In 2010, an estimated 34 million people were living with HIV, around 70% of whom live in sub-Saharan Africa. Furthermore, in 2009 there were an estimated 1.2 million new HIV-associated TB cases, and tuberculosis (TB) accounted for 24% of HIV-related deaths. By the end of 2010, 6.6 million people were taking antiretroviral therapy (ART), around 42% of those in need as defined by the 2010 World Health Organization (WHO) guidelines. Despite this achievement, around 9 million people were eligible and still in need of treatment, and new infections (approximately 2.6 million in 2010 alone) continue to add to the future caseload. This combined with the international fiscal crisis has led to a growing concern regarding weakening of the international commitment to universal access and delivery of the Millennium Development Goals by 2015. The recently launched UNAIDS/WHO Treatment 2.0 platform calls for accelerated simplification of ART, in line with a public health approach, to achieve and sustain universal access to ART, including maximizing the HIV and TB preventive benefit of ART by treating people earlier, in line with WHO 2010 normative guidance. The potential individual and public health prevention benefits of using treatment in the prevention of HIV and TB enhance the value of the universal access pledge from a life-saving initiative, to a strategic investment aimed at ending the HIV epidemic. This review analyzes the gaps and summarizes the evidence regarding ART in the prevention of HIV and TB.